Parental expressed emotion and treatment outcomes in adolescents with autism spectrum disorder - Bigner, Joshua, author; Hepburn, Susan, advisor; Barrett, Karen, committee member; Essert, Deborah, committee member (Colorado State University. Libraries, 2020)
This study uses a case series design to explore the effects parental expressed emotion has on the parent-child relationship and the effects of the outward affect on the treatment outcomes of interventions focused on improving youth coping skills. This paper explores the relationship between the frequency of negative expressed emotions of parents raising children with Autism Spectrum Disorder and the youth's treatment outcomes achieved within a parent-child intervention delivered via telehealth. Characteristics of ASD have far-reaching effects on behavior, particularly in social interactions, such as the ongoing interactions of parents and children within a family. The parents' stress often influences these behaviors. During adolescence, parents often experience high stress due to adolescents' needs for independence and the behaviors associated with puberty. This parenting stress is thought to be heightened if the adolescent is diagnosed with Autism Spectrum Disorder. When parents are stressed, it can increase their negative perceptions of their son or daughter, which likely alters how parents behave towards their children and may be associated with increases in the youth's negative behaviors towards their parent (C. Smith et al., 2018).